Understanding academic help-seeking among first-generation college students: a phenomenological approach - Ruihua, Li; Che Hassan, Norlizah; Saharuddin, Norzihani (Springer Nature, 2025)
Seeking academic help is a common practice for students to achieve academic success. Although there are some studies on academic help-seeking, current research has not fully examined this behavior from the perspective of first-generation college students. This study explores how first-generation college students perceive and engage in academic help-seeking, aiming to understand the factors that influence their attitudes and behaviors in seeking academic support. Semi-structured interviews were conducted with 20 participants, guided by the Theory of Planned Behavior. The interviews were recorded and transcribed, then analyzed using Interpretative Phenomenological Analysis. The findings are as follows: (1) Positive perception, (2) Negative perception, (3) Social Expectations and Pressures in Help-Seeking, (4) Motivators for Help-Seeking, and (5) Inhibitors for help-seeking. Most students have a favorable view of seeking help, but many associate it with self-doubt and concerns about peers’ opinions. Subjective norms in help-seeking are shaped by social expectations and pressures, with key influences coming from family, teachers, and peers. Motivation to seek help affects understanding academic needs, problem-solving urgency, and confidence. However, there are inhibiting factors such as emotional barriers, perceived independence, and concerns about help effectiveness. This study provides valuable insights into the complex dynamics of academic help-seeking among first-generation college students. It highlights their positive attitudes and the multifaceted factors influencing their help-seeking behavior. The insights from this study are critical to developing targeted educational approaches and support mechanisms to assist first-generation college students in their academic endeavors more effectively.